florio® HAEMO: A Longitudinal Survey of Patient Preference, Adherence and Wearable Functionality in Central Europe - Zapotocka, Ester; Batorova, Angelika; Bilic, Ernest; Boban, Ana; Ettingshausen, Carmen Escuriola; Kotnik, Barbara Faganel; Hrdlickova, Radomira; Laguna, Pawel; Máchal, Jan; Nemes, Laszlo; Zupan, Irena Preloznik; Puras, Gediminas; et al. (Advances in therapy, 2024)
INTRODUCTION: florio® HAEMO is a hemophilia treatment monitoring application (app) offering activity tracking and wearable device connectivity. Its use might support everyday activities for people with hemophilia. The aim of this study was to evaluate user satisfaction, long-term usage and the impact on data entry when pairing a wearable with a hemophilia monitoring app. METHODS: This is a follow-up of a two-part user survey conducted in Central Europe. People with hemophilia and parents/caregivers of children with hemophilia using florio HAEMO and who completed part one were invited to complete a second online questionnaire at least 4 months later. RESULTS: Fifty participants (83.3%) who completed part one of the survey continued to use the florio HAEMO app and completed part two. Of 14 participants who chose to use the app with a wearable, more than half (57.1%) were aged between 13 and 25 years. Overall, the results demonstrated that florio HAEMO is very easy or rather easy to use, especially for individuals pairing the app with a wearable. Most people using a wearable indicated that florio HAEMO was very or rather important in bringing certainty to daily activities (85.7%). Notably, 14 of 36 (38.9%) non-wearable users indicated that they would prefer to pair the app with a wearable in the future. CONCLUSIONS: Adherence to the florio HAEMO app is maintained over an extended period of use. Pairing the app with a wearable might enable easier access to app features, increase data entry motivation and provide more certainty about daily activities for people with hemophilia.
Keywords: Wearable Electronic Devices; longitudinální studie; Hemophilia; pacientova volba; Patient Preference; Europe; mladiství; Patient Satisfaction; Evropa; adherence pacienta; průzkumy a dotazníky; Middle Aged; mužské pohlaví; Hemophilia A; hemofilie A; mladý dospělý; Adult; mobilní aplikace; Florio HAEMO; dítě; Child; Young Adult; ženské pohlaví; Humans; Adherence; Wearable; Surveys and Questionnaires; Patient Compliance; lidé středního věku; spokojenost pacientů; Longitudinal Studies; dospělí; nositelná elektronika; Female; Adolescent; Mobile Applications; lidé; Male; Patient satisfaction